Exploration and practice of the path of joint construction of party building between universities and enterprises - Yi, Haibo; Qu , Tao; Huang, Rui; Li , Ningbo; Lin , Weipeng; Huang , Dan; Li , Peidong; Deng , Weiping (International Journal of Engineering and Technology, 2024)
As a new driving force for the innovative development of vocational education, new quality productivity has clarified the main direction of vocational education in serving economic and social development and the main battlefield for cultivating high-quality technical and skilled talents. This article delves into the path and practice of university-enterprise party building collaboration in vocational colleges from the perspective of new productivity. By analyzing the current problems in the joint construction of party building between universities and enterprises in vocational education, exploring and constructing the basic principles, models, and effectiveness evaluation system of the joint construction of party building between universities and enterprises that are suitable for the development of new quality productivity, and forming a practical path, it will promote the deep cooperation between universities and enterprises, achieve the optimal allocation of educational resources, provide beneficial reference and lessons for vocational colleges and enterprises, and also provide strong support for promoting the development of new quality productivity.